KEMUNGKINAN PENGGUNAAN ANTIOKSIDAN GUNA MEMPERTINGGI KETAHANAN OKSIDASI BIODIESEL DARI MINYAK BIJI TANAMAN JARAK PAGAR (Jatropha curcas L.) - Han Roliadi; R. Sudradjat; Arum Anggraini (Jurnal Penelitian Hasil Hutan, 2012)
The excperiment has been done to look into the utilization of Jatropa curcas oil for biodiesel as the alternative of the fossil-based diesel oil through the estrans (esterification and transesterification) process and the use of antiocidants. The estrans process brought about favorable changes in the oil characteristicus (eg, the decreases in density, viscosity, acid number, and iod number), thereby enhancing its performance as biodiesel. Three kinds of antioxidants were used (i.e. TBHQ, BHT, and Formula X), each with varying concentrations (0.03- 0.10%), and storage duration were imposed from the first until fourth week. The examined responses comprised of peroxide number, acid number, and kinematic viscosity. Reaching the fourth week, however, the wcidation process still occurred to the biodiesel oil despite using antioxidants (slight increases in peroxide number, acid number, and kinematic viscosity), but with the intensity far less than that of the control biodiesel (without antioxidant). The antioksidant regarded as the most effective inhibiting, such oxidation was TBHQ, followed in decreasing order by BHT and Formula X. However, the Formula X could expectedly perform as effectively as TBHQ and BHT, but with higher concentration (0.10%). The characteristics of biodiesel either the control or with antisocidants (up to the fourth week duration) could still satisfy the SNI criteria and those of fossil-based diesel oil.